Significance of 18F-fluorocholine PET/CT positive pulmonary lesions in prostate cancer patients - Rager, O.; Baskin, A.; Amzalag, G.; Buchegger, F.; Miralbell, R.; Ratib, O.; Zilli, T.; Garibotto, V. (Nuklearmedizin - NuclearMedicine, 2015)
Aim: To assess the frequency and the significance of incidental pulmonary lesions with 18F-fluorocholine (18F-FCH) PET/CT in prostate cancer (PCa) patients. Patients, methods: 225 consecutive PCa patients referred for 18F-FCH PET/CT (median age 68 years) were retrospectively evaluated for the presence of lesions in the lungs: 173 referred for restaging and 52 for initial staging regarding their high risk of extra prostatic extension. The final diagnosis was based on histopathological or on clinical and radiological follow-up. Results: 13 patients had 18F-FCH positive pulmonary and 8 patients malignant lesions: 5 patients (38%) had a primary lung cancer (2 squamous cell carcinomas, 1 papillary adenocarcinoma, 1 typical pulmonary carcinoid, 1 bronchioloalveolar carcinoma) and 3 patients (23%) PCa metastases. Benign lesions were found in 5 subjects (38%). SUVmax and maximum diameter were neither significantly different in primary and metastatic tumors nor between malignant and benign lesions. Conclusions: Although our results suggest that incidental uptake in the lungs in PCa patients are nonspecific, their detection may have a significant impact on patient management knowing that more than 60% represent malignant diseas.
Keywords: 18F-Fluorocholine; PET/CT; pulmonary metastases; prostate cancer; lung cancer